THE IMPACT OF THE CHANGE OF THE TAX BURDEN ON THE RELIABILITY OF FINANCIAL INFORMATION: THE CASE OF LITHUANIA - Gipiene Gailute; Matusevicienė Lina; Buzinskiene Rita (European Scientific Journal, ESJ, 2013)
This article presents consequences of the change of the tax burden, analyzes the changes of the tax burden in Lithuania, evaluates the impact of the change of the tax burden on the reliability of the financial information by using the example of Lithuanian enterprises in order to discover whether the tax burden alteration results in changes of the reliability of financial information. It was established that enterprises tampering with labor relations-connected revenue also tamper with activity revenue and expenses, i.e. all the three infringements are usually parallel and simultaneous. It was established that financial information presented by enterprises is unreliable because of the evasion of the tax burden, i.e. on the grounds of this information, information users would take incorrect decisions. The completed research leads to a statement that hypotheses stating that with the decrease of the natural person income tax, state social insurance and mandatory health insurance payments as well as the profit tax, enterprises should not evade the burden of these taxes and the financial information regarding this aspect should be reliable are rejected while the hypothesis claiming that there is a trend of the increase of the value added tax testifying the unreliability of the financial information is confirmed.